Assessment of Buckling Failure in Oil Storage Tanks: Finite Element Simulation of Combined Internal and External Pressure Scenarios - Mashiyane, Themba; Tartibu, Lagouge; Salifu, Smith (Science, Engineering and Technology, 2024)
Investigating the structural behaviour and buckling susceptibility of cylindrical oil storage tanks is crucial for ensuring their safe and reliable operation. In this study, the structural behaviour and buckling susceptibility of closed roof-top cylindrical oil storage tanks under combined internal and external pressure scenarios were investigated using the finite element analysis (FEA) technique. By utilizing the FEA technique, the combined effect of wind-induced pressure of 250 Pa, applied on the outer surface of the tank and internal pressure of 0.5 MPa, applied on the outer surface of the storage was analysed. The result reveals significant stress concentrations and deformation patterns, particularly on the windward side of the tank, thus, emphasizing the susceptibility of the storage tank to buckling under the specified operating conditions for both the filled and half-filled tank; with internal pressure emerging as the primary contributor to mechanical strain and deformation experienced in the tank, while the wind load plays a secondary but significant role in the deformation of the tank. The fe-safe predicted useful life shows that under the specified operating conditions, the filled storage tank will survive 1 429 hours (2 months) while the half-filled tank will survive 3 551 hours (5 months) before failure due to buckling. Thus, the useful life estimation results show the importance of varying oil levels and operating conditions in the structural assessments of storage tanks.